Hospitals as Public Legal Subjects within the State Administrative Law Regime: Rumah Sakit sebagai Subjek Hukum Publik dalam Rezim Administrasi Negara - Zulkarnain, Hadi (Fakultas Hukum Universitas Jambi, 2026)
The rapid development of information technology has shifted the pattern of medical dispute resolution from formal institutional mechanisms to digital public spaces through online media. This transformation generates significant legal implications, particularly concerning administrative legal protection for physicians and hospitals as public service providers in the health sector. This study aims to examine the legal standing of hospitals within the framework of administrative law and to formulate the construction of administrative legal protection afforded to physicians and hospitals in addressing medical disputes disseminated through online media. This research employs a normative legal method using statutory, conceptual, and case approaches. The legal materials consist of legislation governing health services, medical practice, press law, and electronic information and transactions, as well as doctrines of administrative and health law. The findings demonstrate that hospitals possess a dual legal character: as private legal entities performing public functions based on state-attributed and delegated authority. Consequently, their actions are subject to the principles of legality, accountability, and administrative supervision. Medical disputes circulating in digital platforms are generally triggered by deficiencies in therapeutic communication, differing interpretations of medical risk and malpractice, and the rapid formation of public opinion prior to normative verification. Administrative legal protection may be implemented through preventive mechanisms, including the right of reply and alternative dispute resolution, while repressive measures must be applied proportionately as an ultimum remedium. An administrative law approach provides a structured and balanced framework to ensure legal certainty, justice, and sustainability in health service delivery in the digital era.